ISSUE IN MERDEKA CURRICULUM: ANXIETY LEVELS OF EFL TEACHERS IN INDONESIAN JUNIOR HIGH SCHOOLS - Khasanah, Tanti Nur; Anugerahwati, Mirjam; Karmina, Sari (Erudio Journal of Educational Innovation, 2024)
The lack of highlight on teachers’ psychological aspects in scientific study triggers the urgency to frame their teaching anxiety. In Indonesian context, educational sectors adapt new curriculum that motivates teachers to create innovations. Unfortunately, the trends center students’ aspects and exploration on teachers’ wellbeing is underexplored. Therefore, this study is objectively aimed to reveal the anxiety levels of EFL teachers in ELT practices under the influence of Merdeka curriculum in junior high schools and to scrutinize the significant differences of their anxiety levels based on the vary of demographic profiles. Quantitative research with survey design was conducted by spreading online and offline 5-points Likert scales of FLTAS (Foreign Language Teaching Anxiety Scales) questionnaire modified from Aydin & Uştuk (2020), to the 60 EFL teachers in Surakarta who professionally experienced in adapting the new curriculum. The data were analyzed by running descriptive analysis, t-test, and ANOVA on SPSS v.29.0. The results showed that teachers performed low frequent anxiety levels on language proficiency (=1.73-2.27), teaching experience (=1.65-2.07), apprehension of evaluation (=1.98-2.23), and time management (=1.93-2.08). Interestingly, they reported high frequent anxiety regarding issues of students’ interest (=2.78-3.13). The demographic backgrounds on gender, school types, and teaching experiences contributed significant variations on their anxiety. The further findings and discussions are portrayed on the following reports.